Do learners with higher readiness feel less anxious when studying online at home? - Qin, Chao; He, Hao; Zhu, Jiawen; Hu, Jie; Yu, Jia (Frontiers in Psychology, 2022)
In response to the COVID-19 outbreak in many parts of the world, online education has become a more viable option. Some studies have assessed undergraduate students' readiness for online learning, while others examined students' anxiety about online learning at home. The relationship between readiness and anxiety about online learning is, however, not well explored. This paper has two purposes: (1) to develop a new and valid instrument—the Home-based Online Learning Readiness Questionnaire (HOLRQ)—to measure students' readiness to study online at home based on a theoretical framework of self-regulated learning. As a replacement for the previous readiness scale, this new instrument adds a section on learning strategies and updates and develops new items. (2) to investigate the relationship between readiness and anxiety in online learning. In order to explore those issues, 527 undergraduate students in China were surveyed in this study. The results indicated that HOLRQ were validated in the following six domains: motivation, self-efficacy, information technology skills, resource management, learning strategies and help-seeking. Chinese undergraduate students were more prepared in resource management, motivation, and help seeking, but less prepared in learning strategies, information technology skills, and self-efficacy. However, the regression analysis showed that readiness did not predict online learning anxiety. It means even highly prepared self-regulated learners may experience anxiety when learning online from home. The findings provide insights for instructors and administrators determine how students really feel about learning from home with online education.